2021
DOI: 10.3390/ijerph18073737
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of High-Risk Sexual Behavior among Polish University Students

Abstract: High-risk sexual behavior consists of activities and habits that put a person at increased risk of sexually transmitted infections (STIs) or unplanned pregnancy. Poland is currently experiencing a problem with increased STI rates, largely due to poor sexual education. Our exploratory study aims to evaluate the sexual behavior of students attending universities across Poland. The study covered 7678 students from 50 different faculties and universities across the country. The authors created an original question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
2
16
0
2
Order By: Relevance
“…This difference with the Bangkok study may be due to varying socio-demographic and cultural context between the two study areas. A study in South Korea [23], found that only 5% of high school students were sexually active, which is in stark contrast to a study in the Poland where more than 78% of students attending universities had ever had sex [24]. It is not clear whether these wide differences in sexual activity are attributed to different de nitions of sex, time period, or other differences among sample populations and data collection methods.…”
Section: Discussionmentioning
confidence: 84%
“…This difference with the Bangkok study may be due to varying socio-demographic and cultural context between the two study areas. A study in South Korea [23], found that only 5% of high school students were sexually active, which is in stark contrast to a study in the Poland where more than 78% of students attending universities had ever had sex [24]. It is not clear whether these wide differences in sexual activity are attributed to different de nitions of sex, time period, or other differences among sample populations and data collection methods.…”
Section: Discussionmentioning
confidence: 84%
“…This difference with the Bangkok study may be due to varying socio-demographic and cultural contexts between the two study areas. A study in South Korea [ 23 ], found that only 5% of high school students were sexually active, which is in stark contrast to a study in the Poland where more than 78% of students attending universities had ever had sex [ 24 ]. It is not clear whether these wide differences in sexual activity are attributed to different definitions of sex, difference in age of the samples, or other artifacts of the studies.…”
Section: Discussionmentioning
confidence: 92%
“…The findings set the direction for research carried out in groups of adolescents around the world, including students. The largest part of studies related to risky sexual behaviours in this group concerned the following issues (most often considered together): early sexual initiation, frequency of vaginal, oral and anal unprotected intercourse, number of sexual partners, sexual contacts with random partners and the use of contraception [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The basic conclusion drawn from the research is that students are a group who is particularly prone to engaging in risky sexual behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…They were usually individual determinants: related to the characteristics of the respondents (e.g., gender, age, sexual orientation) or experiences of other risky behaviours (e.g., getting drunk, using drugs, participating in fights, participating in discos [ 26 , 29 ]. The social context, including family and peers, was taken into account much less often [ 22 , 24 , 26 , 27 ]. Some studies also concerned the relation between childhood abuse [ 30 ] and attachment style [ 31 ] in terms of risky behaviours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation